Scapegoating of ethnic minorities: Experimental evidence - Tomáš Želinský; Gerard Roland; Jana Cahlíková; Julie Chytilová; Michal Bauer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Scapegoating refers to a social phenomenon whereby members of an aggrieved majority group retaliate against innocent third parties, usually members of vulnerable minority groups. This column uses an experiment set up between May and September 2017 in Eastern Slovakia – where a large Roma minority regularly suffers from discrimination – to measure how an injustice that affects a member of one's own group shapes the punishment of an unconnected bystander (or scapegoat). The experiment shows that members of a majority group will systematically shift punishment onto innocent members of an ethnic minority.
Keywords: 330